Translating Malay Compounds into Arabic Based on Dynamic Theory and Arabization Method - Wahiyudin, Ummi Nadjwa; Muhamad Romli , Taj Rijal Bin (Journal of Islamic Thought and Civilization, 2021)
This study aims at making possible the effective use of machine translation (MT) in interpreting the Malay compounds into Arabic ones following the structure and Arabic style. The necessity of this study arises on account of the weakness of translation quality using online MT and the lack of suitable methods to structure the compounds from the Malay language into Arabic. There are three objectives of this study which are to collect the results of Malay compound translations using online MT into Arabic, analyze the results of the compound translations, and suggest compound translation methods based on dynamic theory and Arabization method. The study uses three online MT as instruments to translate: Google Translate, Microsoft Bing Translator, and Yandex Translator. This qualitative study employs a descriptive approach and analysis method in collecting information and analyzing data. The study focuses on 15 Malay compounds which are later categorized into school names, hospital names, and clinics. The findings of translation have been drawn using the next three MTs and analyzed at three main level: namely grammar level, phonetics and phonology level, and dynamic translation level. From this analysis, 4 out of 15 compound nouns translations data into Arabic are categorized as poor translations for not approaching the structure and Arabic style. In the final stages, the results of the translation collected are formulated and suggested alternative translations based on dynamic theory and methods of Arabization and compound restructuring formula in Arabic. Through this process, the translation results of the compounds can be categorized as translations that can meet the structure and style of the Arabic language. The compound translation model can be proposed as a new translation method for Arabic language users, especially the Arabic translators and students both at school and higher education. Keywords: Translation, Compounds, Machine translation, Arabization